Repeatability and precision in proboscis length measurements for long proboscid flies - Morita, Shelah I. (Zootaxa, 2011)
Methods for measuring proboscides in long-tongued fly pollinators are examined with respect to fly morphology and behavior. Most ecological studies aim to measure the functional proboscis length as a response or predictor variable. Here I suggest a proxy for this, the Maximum Functional Length (MFL), obtained by combining the lengths of the prementum and labrum. I also quantify errors in proboscis measurements due to a lack of consideration of the extensible ventral rostral membrane (VRM). Results show that naïve measurements allow for substantial unrepeatable variation (mean: 7mm; maximum 14mm).